Demographic Characteristics of Population in Telangana State of India: A Regional Analysis - Singh, Binod Kumar; Bilas, Ram (National Geographical Journal of India, 2022)
The population of Telangana is works out to be 35.2 million in 2011. The population of Telangana has increased by 4.2 million during the decade 2001-2011. Telangana is the twelfth most populous state of India. A little more than one out of every thirty-four persons in India is from Telangana. Spread over 115 thousand square kilometres, Telangana hosts a population density of 306 persons per square kilometres as per Census of India, 2011. Of the total population, over three-fifth is confined to less developed Telangana Plateau region comprising of 6 out of 10 districts. The most conspicuous feature of the demographic characteristics of Telangana is its unevenness and highly irregular spatio-temporal character. Therefore, in this paper an attempt is made to analyse the major demographic characteristics of Telangana. The data are analysed and compared regionally to understand the regional variations in the size, growth, distribution, age-sex distribution, dependency burden, literacy rate by sex, work participation by sex, religious composition, social structure, urbanisation and population density. For this purpose decennial census data have been used extensively with the methods used in demographic analysis. In this paper all parameter aggregate are estimated at the level of the state and region for ready comparisons from the district level census figures.